PRESSURE-INDUCED IONIZATION OF NICKEL DEEP LEVELS IN COMPENSATED SILICON UNDER HYDROSTATIC PRESSURE: A STATIC REGIME STUDY - R. Khamidov,; J. Nematullaev, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract:The piezoresistance effect in n-type silicon compensated with nickel (n-Si:(P,Ni)) has been investigated under static hydrostatic pressure conditions. The static regime, characterized by slow pressure application rates (